Boundary Crossing and the Professional Learning of Teacher Educators in New International Contexts. Issue 2 (3rd May 2016) - Williams, Judy; Berry, Amanda
Abstract: In this collaborative self-study, two teacher educators examine their experiences of working in new international contexts and the impact of those experiences on their professional learning and identities. Mandi moved from a major research university in one country to another, while Judy co-led a group of pre-service teachers on an international practicum for three weeks each year for three years. Using the concept of boundary crossing as a theoretical and analytical framework, each teacher educator identified a boundary-related critical incident or experience that occurred during her work in new international contexts. Through individual and collaborative analysis of their critical incidents, they found that working as a teacher educator in new international contexts involves the crossing and re-crossing of multiple personal, professional, linguistic and cultural boundaries. Working in these boundary spaces involved learning how to negotiate new kinds of relationships with colleagues and students, manage changed roles and responsibilities and, ultimately, a search for a renewed sense of self, as each sought to understand herself differently within a new professional context.